Chromium contamination in paddy soil-rice systems and associated human health risks in Pakistan - Ali, W.; Zhang, H.; Mao, K.; Shafeeque, Muhammad; Aslam, M. W.; Yang, X.; Zhong, L.; Feng, X.; Podgorski, J. (Elsevier, 2022)
Chromium (Cr) contamination in paddy soil-rice systems threatens human health through the food chain. This study used a new dataset of 500 paddy soil and plant tissue samples collected in the rice-growing regions of Sindh and Punjab Provinces of Pakistan. Overall, 97.4% of grain samples exceeded the Cr threshold values of 1.0 mg kg-1, determined by the China National Food Standard (CNFS). The Cr in paddy soil, 62.6% samples exceeding the China natural background threshold value (90 mg kg-1) for Cr concentration in paddy soil, and lower than the (pH-dependant > 7.5 threshold value for Cr 350 mg kg-1) as determined by China Environmental Quality Standards (EQSs) for paddy soil (GB15618-2018). Geographically weighted regression (GWR) modelling showed spatially nonstationary correlations, confirming the heterogeneous relationship between dependent (rice grain Cr) and independent paddy soil (pH, SOM, and paddy soil Cr) and plant tissue variables (shoot Cr and root Cr) throughout the study area. The GWR model was then used to determine the critical threshold (CT) for the measured Cr concentrations in the paddy soil system. Overall, 38.4% of paddy soil samples exceeding CT values confirm that the paddy soil Cr risk prevails in the study area. Furthermore, the GWR model was applied to assess the loading capacity (LC), the difference between the CT, and the actual concentration of Cr in paddy soil. Loading capacity identified potential paddy soil Cr pollution risk to rice grain and assessed the risk areas. Overall LC% of samples paddy soil Cr risk areas grade: low-risk grade I (34.6%); moderate-risk grade II (15.8%); high-risk grade III (11.2%); and very high-risk grade IV (38.4%) have been assessed in the study area. The human health index, total hazard quotient (THQ « 1), indicates no potential health risk originating from Cr exposure to the population. However, the excess Cr level in paddy soil and rice grain is still a concern. The current study's results are also valuable for the national decision-making process regarding Cr contamination in the paddy soil-rice system.